PENGARUH KEAHLIAN TEKNIS DAN NON TEKNIS TERHADAP KINERJA PEGAWAI SATUAN KERJA PELAKSANAAN JALAN NASIONAL WILAYAH III SULTENG - Andriyadi, Opik Taopik (Katalogis, 2015)
The objectives of this research are: 1. To explore and analyze simultaneous effects of technical and non-technical skills on employees’ performance at The National Road Work Unit Region III Central Sulawesi; 2. To explore and analyze the effect of technical skills on employees’ performance; 3. To explore and analyze the effect of non-technical skills on employees’ performance; 4. To explore and analyze the dominant variable that affects the employees’ performance. As an explanatory research, which shows the relationship between variables, the research selected 73 respondents by census sampling method as its samples. Based on multiple linear regressions, the results indicate that: 1. Technical and non-technical skills simultaneously have significant effects on employees’ performance at The National Road Work Unit Region III Central Sulawesi; 2. Technical skills have significant effect on employees’ performance; 3. Non-technical skills have significant effect on employees’ performance; 4. Non-technical skills have dominant and significant effect on employees’ performance.